The relationship between education and economic growth: A cross-country analysis (Research, Society and Development, 2023)
This study investigates the effects of education on economic growth in 89 low, middle, and high-income countries using an index of human capital developed by Penn World Table and economic growth data from the World Bank’s World Development Indicators. This study specifies a growth accounting empirical model to examine the effects of education on economic growth. Using systems Generalized Method of Moments estimation technique on annual data covering the periods from 2002 to 2020, the results show that education significantly enhances economic growth. On average, an increase in the education index by 0.1 increases the growth of real GDP per capita by 0.8 percentage points. The results also show that education does have higher returns for low- and middle-income countries compared to high-income countries. The results of this study lend credence to the argument that poor countries should focus and pool adequate resources towards education as a means to achieving growth.